Direct heating pattern on graphene oxide film to build flexible micro-supercapacitors. (30th April 2021) - Peng, Cheng; Li, Qiang; Niu, Liang; Yuan, Hong; Xu, Jiahui; Yang, QingQing; Yang, YuanJun; Li, Guoxiang; Zhu, Yanwu
Abstract: The development of portable and wearable electronic devices continues to increase the demand for miniature energy storage units. Here, we fabricate the flexible micro-supercapacitors (MSCs) through direct heating pattern on graphene oxide film. The shape designable MSCs are based on planar reduced graphene oxide/graphene oxide (rGO/GO) structure, with rGO as electrode and GO as separator. The GO area heated by heating pen is reduced to rGO, and the area with no heating is still GO. The interdigitated MSC made at 400 °C delivers high area capacitance of 94.8 mF cm −2 at current density of 0.25 mA cm −2 within poly(vinyl alcohol) (PVA)/H2 SO4 gel electrolyte. It provides high energy density of 10.7 mWh cm −2 at power density of 112.6 mW cm −2 . In addition, it also has excellent mechanical stability, with basically unchanged area capacitance from 0° to 180° bending angles. The MSCs with shapes of spiral, concentric circle and eight-trigrams are also fabricated via this method. The results indicate that heating pattern on GO films to build flexible MSC is a promising and low-cost new method to fabricate energy storage equipment for future electronic devices. Graphical abstract: Image 1